HOW NATURE’S INGENIOUS DESIGN PRINCIPLES IN FASHION INSPIRE SUSTAINABLE SOCIAL AND ENVIRONMENTAL TRANSFORMATION - Jha, Rahul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The global fashion industry is both a driver of cultural expression and a major contributor to environmental and social challenges. Responsible for substantial water consumption, wastewater generation, and textile waste, it faces urgent calls for sustainable transformation. Biomimicry, design inspired by nature’s models, systems, and processes, offers a compelling pathway for such change. By replicating natural efficiencies such as the lotus effect for self-cleaning fabrics, spider silk’s tensile strength for lightweight yet durable materials, and closed-loop cycles found in ecosystems, biomimetic design can reduce environmental impact while fostering social awareness and ethical consumer behavior. This paper synthesizes research on biomimetic materials, case studies, and industry trends, highlighting how nature’s principles can transform fashion into a regenerative, socially responsible sector. Quantitative analyses demonstrate the potential for significant reductions in water consumption, energy use, and waste generation through biomimetic innovation. The discussion also explores the social dimensions, from consumer awareness to equitable production practices, and outlines policy and design recommendations for scaling these approaches.